The Multinational Corporation as a Third Space: Rethinking International Management Discourse on Knowledge Transfer Through Homi Bhabha - Frenkel, Michal (Academy of Management Review, 2008)
In this paper I use insights from postcolonial scholar Homi Bhabha to analyze international management discourse on the cross-national transfer of knowledge and practices within the multinational corporation. Stressing the increasing importance of first world–third world geopolitical relations in shaping the transfer process, I apply Bhabha's epistemology of mimicry, hybridity, and the third space to offer an alternative understanding of the transfer process itself, the nature of the organization within which this process takes place, and the notions of power and agency as they are currently understood in international management studies.